ANALISIS RASIO-RASIO KEUANGAN UNTUK MEMPREDIKSI FINANCIAL DISTRESS BANK DEVISA PERIODE 2006 2011 - Agus Baskoro Adi (STIE Perbanas Surabaya, 2014)
There are some studies describing prediction models of banks bankruptcy, but only few have sought to predict banks financial distress which happens before bankruptcy. This study examines the factors affecting financial distress condition of foreign banks in the periods of 2006 2011. The tested factors are the changes of median value of Equity, the changes ofmedian value of Net Interest Margin and the changes of median value of Return on Equity. Variables used in this study consist of CAR, NPL, ROA, NIM, ROE, LDR, and IRR. The sample consists of 166 banks categorized as foreign banks in Indonesia in the periods of 2006 2011, collected by purposive sampling. The logistic regression was used for analyzing the data and backward stepwise technique is used to gain a model that has the highest classification power, by removing the most insignificant variable in a model. The results show that Return on Asset (ROA), Return on Equity (ROE) and Net Interest Margin are significant variable. The insignificant variables are CAR, NPL, LDR and IRR. This research also indicatesthat not all the variables tested can predict the financial distress of foreign bank.